Association of fetal biparietal diameter with mode of delivery and perinatal outcome. (2nd February 2016) - Bardin, R.; Aviram, A.; Meizner, I.; Ashwal, E.; Hiersch, L.; Yogev, Y.; Hadar, E.
ABSTRACT: Objective: To determine the association between sonographic assessment of fetal biparietal diameter (BPD) and pregnancy outcome. Methods: This was a retrospective cohort study of pregnancies at 37–42 weeks of gestation which had antepartum sonographic measurement of BPD within 7 days before delivery. Eligibility was limited to singleton pregnancies with neither known structural or chromosomal abnormalities nor prelabor Cesarean delivery (CD). The association of BPD with outcome was analyzed using multivariate logistic regression, receiver–operating characteristics curves and stratification according to BPD quartiles. Results: In total, 3229 women were eligible for analysis, of whom 2483 (76.9%) had a spontaneous vaginal delivery (SVD), 418 (12.9%) underwent operative vaginal delivery (OVD) and 328 (10.2%) underwent CD. The mean BPD in the obstetric intervention groups (OVD and CD) was significantly higher than that in the SVD group ( P < 0.001). After adjusting for confounders, increased BPD was an independent risk factor such that higher values of BPD were associated with progressively higher risk of obstetric intervention (adjusted odds ratio, 1.05 for each 1‐mm increase in BPD (95% CI, 1.02–1.09)), but no clear cut‐off value for obstetric intervention was found. The fourth quartile group (BPD ≥ 97 mm) was associated with a significantly lower SVD rate ( P < 0.001) and higher OVD rate ( P = 0.04), relative to the first (BPD 88–90 mm) and second (BPD 91–93 mm) quartile groups, with no apparent adverse impact on immediate neonatal outcome. Conclusions: Increased BPD within the week prior to delivery is an independent risk factor such that higher values of BPD are associated with progressively higher risk of obstetric intervention; however, in our experience, no adverse neonatal outcome resulted from such intervention. Thus, increased BPD should not discourage a trial of vaginal delivery. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.